Andrzej Rudomina—unforgettable Lithuanian Jesuit missionary scholar: from Vilnius University to China - Konior, Jan (Acta Orientalia Vilnensia, 2009)
Jesuit University of Philosophy and Education ‘Ignatianum’ This paper explores one of great Lithuanian Jesuit missionaries to China—Andrzej Rudomina (Lith. Andrius Rudamina, Chin. Lu an de) 盧安德 (1595–1631)—also providing a look at the cultural and spiritual background of Lithuania and Poland in which he was brought up. It also shows the situation of the Society of Jesus in the 16th and 17th centuries, with particular focus on the Lithuanian–Polish–Chinese context and connection. Andrzej Rudomina was the first Lithuanian Jesuit to set foot behind the Great Wall of China in the 17th century. In 1625 he reached Goa, and then Macau, before studying Chinese literature in Nankeen Province. There he began to immerse himself in the complexities of Chinese customs. The natives called him Lu an de (the Chinese name of Andrzej Rudomina). He reports participating in the Kating Conference (1627), at which was sought the Chinese equivalent for the name of the Lord our God, Tian Zhu 天主. He was very much valued by his Jesuit brothers and by the Chinese. He died prematurely at the age of 35 of tuberculosis. This article will explore the life of Rudomina. We will try to understand this man of holiness, mobility and disponibility. He was a man on mission, but what was nature of the mission and who was it for? What does he have to tell us today in the 21st century? What kind of sign is he for us today?